A lumped parameter model for disk brake squeal and its suppression through use of dither signals. (1st January 2011) - Shahin, Bahram; Ziaei-Rad, Saeed; Esfahanian, Mohsen
This paper presents a model for reducing the brake squeal by utilising a harmonic force, the so-called dither force. Two different positions for the dither force were considered, namely perpendicular and parallel to the braking pressure. As this harmonic force is applied to the brake system by piezoelectric actuator that is fixed in the piston of the brake system, therefore, the parallel configuration is more practical. The equations of motion for both cases were solved and it was shown that even by applying a large force, the stick-slip phenomena cannot be suppressed completely. Next, the sliding mode and computed torque method control strategies were applied to the system with parallel configuration. The results indicate that both methods can effectively suppress the brake squeal.